Experimental Infection of Indigenous Climbing Perch Anabas testudineus with Aeromonas hydrophila Bacteria - Hossain, M Farhad; Rahman, M Mamnur; Sayed, MA (Progressive Agriculture, 2013)
The present study was conducted to know the pathogenicity and LD50 of Aeromonas hydrophila isolated from diseased climbing perch Anabas testudineus against apparently healthy homologous fish and the distribution of the bacteria in the organs of the experimentally infected fish. A total of 10 fish of average body weight of 18 g were used. For pathogenicity test, two different doses viz. 9.2 × 107 and 9.2 × 106 CFU/fish were injected intramuscularly. Pathogenicity of A. hydrophila was confirmed at water temperature of 28.53oC by the mortality of 40% to 100% of all tested fish within 4 to 9 days. The highest bacterial load was found to be 9.4 × 108 CFU/g in the intestine and the lowest bacterial load was found to be 2.8 × 103 CFU/g in the kidney of the tested fish. Four different serial concentrations, vide 9.2 × 107, 9.2 × 106, 9.2 × 105 and 9.2 × 104 CFU/fish of the bacteria were injected in each of four different groups of 10 fish. The calculated LD50 value at 27.3oC water temperature was 2 × 107 CFU/fish of 18 g of average body weight. In all the cases of intramuscular injection, external pathology was found. Reddish anal region and fin bases were observed. Injected A. hydrophila was re-isolated from liver, kidney and intestine of the challenged fish. It was understood that the isolate was a high virulent pathogen for A. testudineus. DOI: http://dx.doi.org/10.3329/pa.v22i1-2.16472 Progress. Agric. 22(1 & 2): 105-114, 2011